2017
DOI: 10.1016/j.sajb.2016.02.198
|View full text |Cite
|
Sign up to set email alerts
|

Production of dihydrochalcone-rich green rooibos (Aspalathus linearis) extract taking into account seasonal and batch-to-batch variation in phenolic composition of plant material

Abstract: a b s t r a c t a r t i c l e i n f o Available online xxxx Edited by: J. van StadenRandomly selected rooibos plants from three plantations were harvested (a few branches per plant) at intervals from early summer to late spring. The aspalathin and nothofagin content of the plant material was highest at the first harvest date (3.76% and 0.54%, respectively) in summer whereafter their content decreased gradually to the lowest levels in winter and increased to 3.31% and 0.36%, respectively in mid-spring. Commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…tional manner that includes the "fermentation" (oxidation) step for development of the characteristic red-brown leaf colour and "woody", "fynbos-floral", and "honey" flavour [23,24], and contains very little aspalathin (0.02-1.2 %) [20], while the "unfermented product", green rooibos, has an aspalathin content between 2.5 and 4.5 % [25]. Hot water extracts prepared from fermented and green rooibos are used as food and/or cosmetic ingredients.…”
Section: Natural Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…tional manner that includes the "fermentation" (oxidation) step for development of the characteristic red-brown leaf colour and "woody", "fynbos-floral", and "honey" flavour [23,24], and contains very little aspalathin (0.02-1.2 %) [20], while the "unfermented product", green rooibos, has an aspalathin content between 2.5 and 4.5 % [25]. Hot water extracts prepared from fermented and green rooibos are used as food and/or cosmetic ingredients.…”
Section: Natural Sourcementioning
confidence: 99%
“…Hot water extracts prepared from fermented and green rooibos are used as food and/or cosmetic ingredients. If a high aspalathin content is required, a hot water extract (aspalathin content > 8 %) of green rooibos [25] is preferable. On the other hand, a hot water extract (aspalathin content < 2 %) of fermented rooibos [26] is more economical to produce and it is preferred in food products, such as rooibos iced tea, when the flavour is important [27].…”
Section: Natural Sourcementioning
confidence: 99%
“…Analyses with different plant species [37] showed that plant tissues richer in polyphenols yielded higher flow cytometry genome size estimates than plant tissues with low polyphenol contents. In rooibos, aspalathin concentrations have been shown to be higher in leaves than in stems [38], but comparative analyses for seedling tissues are outstanding.…”
Section: Discussionmentioning
confidence: 99%
“…Subchronic feeding of type 2 diabetic model (KK‐A y ) mice with a cold‐water based green rooibos extract containing 66 g kg −1 aspalathin suppressed the increase in their fasting blood glucose levels . Previously, we demonstrated that green rooibos extract containing at least 80 g kg −1 aspalathin was achievable when green rooibos was subjected to a hot water extraction process, similar to that used industrially for the production of food grade extracts of fermented rooibos …”
Section: Introductionmentioning
confidence: 99%
“…This is manifested as a large variation in the AC of their hot water extracts. Only a moderate correlation ( r = 0.695) between the dihydrochalcone (sum of aspalathin and nothofagin) content of the plant material batches and their extracts was obtained, suggesting that other factors play a role that have not been taken into account. Extracts containing a higher than required level of a target bioactive compound could be diluted to meet the specification using an excipient.…”
Section: Introductionmentioning
confidence: 99%